QUANTUM DYNAMICS IN MOLECULAR DIPOLAR SYSTEMS - Mîrzac, Alexandra (My University, 2022)
The detection of new quantum dynamical properties in two and three-level Λ-type systems possessing a non-zero permanent dipole moment strongly coupled with quantum optical cavity or opto-mechanical resonators.
Studiul dinamicii cuantice în sistemele moleculare dipolare
Исследования квантовой динамики молекулярных диполярных систем
Teză de doctor în științe fizice - Conducător de doctorat: dr. hab. în științe fizico –matematice, prof., Mihai MACOVEI.
Keywords: two-level system; quantum interference; multiphoton conversion; quantum emitter; super-Poissonian statistics; laser terahertz; procese cuantice multiple; interferență cuantică; conversia multifotonică; emițător cuantic; генерация фотонов; резонантная флюресценция; квантовый излучатель